Teologi Pembebasan di Amerika Latin: Perspektif Sosiologi Marxis - Mohammad Nuh Hasan (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2002)
Liberation Theology in Latin America emerges as a theological reflection shaped by a socio-political context characterized by oppression, economic disparity, and cultural alienation. This theological movement seeks three interrelated forms of liberation: first, liberation from economic, social, and political oppression; second, liberation from institutionalized violence and dehumanization; and third, spiritual liberation from sin, enabling communion with God and humanity. However, its application has sparked controversy due to its Marxist analytical approach, which promotes political revolution, justifies violence, and challenges ecclesiastical authority. Critics argue that this theological perspective aligns with atheistic, materialistic, radical, and anti-capitalist ideologies, positioning it in opposition to Western thought.